A critical review of chronic traumatic encephalopathy. (September 2015) - Iverson, Grant L.; Gardner, Andrew J.; McCrory, Paul; Zafonte, Ross; Castellani, Rudy J.
Highlights: Chronic traumatic encephalopathy is reported to be a unique neurodegenerative disease. The literature to date is anecdotal and based on autopsy case studies. There is no established methodology to diagnose CTE in a living person. The science relating to CTE is very limited. Abstract: Chronic traumatic encephalopathy (CTE) has been described in the literature as a neurodegenerative disease with: (i) localized neuronal and glial accumulations of phosphorylated tau (p-tau) involving perivascular areas of the cerebral cortex, sulcal depths, and with a preference for neurons within superficial cortical laminae; (ii) multifocal axonal varicosities and axonal loss involving deep cortex and subcortical white matter; (iii) relative absence of beta-amyloid deposits; (iv) TDP-43 immunoreactive inclusions and neurites; and (v) broad and diverse clinical features. Some of the pathological findings reported in the literature may be encountered with age and other neurodegenerative diseases. However, the focality of the p-tau cortical findings in particular, and the regional distribution, are believed to be unique to CTE. The described clinical features in recent cases are very similar to how depression manifests in middle-aged men and with frontotemporal dementia as the disease progresses. It has not been established that the described tau pathology, especially in small amounts, can cause complex changes in behavior such as depression, substance abuse, suicidality, personality changes, or cognitive impairment. Future studies will help determine the extent to which the neuropathology is causally related to the diverse clinical features.